Earnings Management: Disclosure Quality and Director Characteristics - Livia Aldisa Muliawan; Yulius Kurnia Susanto; Dewi Sari Wijoyo (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this research is to get empirical evidence about the influence of disclosure quality and director characteristics on earnings management. Director characteristics are director size, gender, tenure, and independent commissioner. This research used 81 manufacturing companies which are listed in Indonesia Stock Exchange from 2016 until 2018 and selected using purposive sampling method and analyzed using multiple regression. The result of this research found that the effect of director size and tenure on earnings management were negative and significant. The other hand, disclosure quality, director gender, and independent commissioner have not influence to earnings management. The larger the directors size and long as director will make authority become spread and minimize the chance for doing earnings management.